2014
DOI: 10.1371/journal.pone.0091900
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Rules for Pollen and Nectar Foraging Bumblebees – A Laboratory Study with Artificial Flowers Offering Diluted Nectar Substitute and Pollen Surrogate

Abstract: Almost all bees collect nectar and pollen from flowers. Female bees collect pollen to provision their nest cells, whereas they use nectar for individual energy supply and nest cell provisioning. Bees fine-tune nectar foraging to the amount and to the concentration of nectar, but the individual bees' response to variability of amount and concentration of pollen reward has not yet been studied thoroughly in laboratory settings. We developed an experimental set-up in which bumblebees simultaneously collected suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 62 publications
1
59
0
Order By: Relevance
“…Interestingly, higher protein concentrations in modified diets led to fewer feeding events and reduced pollen consumption. It is important to note that in the previous experiments that found increasing protein concentration increased attraction (27,28), the protein composition of the pollen was modified by diluting it with cellulose powder, thereby reducing all nutrient concentrations and sensory cues. Furthermore, our studies demonstrate that B. impatiens does not simply avoid pollen (or diets) with high lipid content: One of their most preferred plant species, T. ohiensis, had relatively high lipid concentrations (Table 1), and they preferentially consumed modified diets with moderate lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, higher protein concentrations in modified diets led to fewer feeding events and reduced pollen consumption. It is important to note that in the previous experiments that found increasing protein concentration increased attraction (27,28), the protein composition of the pollen was modified by diluting it with cellulose powder, thereby reducing all nutrient concentrations and sensory cues. Furthermore, our studies demonstrate that B. impatiens does not simply avoid pollen (or diets) with high lipid content: One of their most preferred plant species, T. ohiensis, had relatively high lipid concentrations (Table 1), and they preferentially consumed modified diets with moderate lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…While foraging in the same landscape, bumble bees foraged preferentially on plant species with higher protein content than did honey bees (25), suggesting species-specific differences in protein acquisition. Bumble bee workers can taste and discriminate among diets with different protein or pollen concentrations (26), and their foraging activity has been positively correlated with pollen protein content using modified (diluted with cellulose powder) single-source pollen diets (27,28) or a single plant species in which pollen protein content varied with soil conditions (20). [Note that in field studies honey bees do not appear to forage preferentially on pollen with higher protein concentrations (29,30)].…”
mentioning
confidence: 99%
“…Evolutionarily, this preference aligns with a goal of providing optimal resources for their brood, because suboptimal pollen quality can lead to reproductive deficit, egg cannibalism, and larval ejection (Génissel, Aupinel, Bressac, Tasei, & Chevrier, 2002; Tasei & Aupinel, 2008). In the laboratory, bumble bees prefer pollen diets with higher protein concentrations (Kitaoka & Nieh, 2008; Konzmann & Lunau, 2014; Ruedenauer, Spaethe, & Leonhardt, 2015; Ruedenauer et al., 2016), and these preferences extend to the field among plant species or within the same species (Cardoza et al., 2012; Hanley et al., 2008). Furthermore, bumble bee colonies will increase their foraging efforts to higher quality pollen (or nectar), or reduce foraging efforts to low‐quality pollen, even if no alternative is available (Dornhaus & Chittka, 2001, 2004; Kitaoka & Nieh, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as they can detect the sugar content of nectar via gustatory receptors on their antennae, mouthparts and tarsi (de Brito Sanchez, 2011), they preferentially collect nectar of high sugar concentrations (Hagler, 1990). Several studies have shown that bees also preferentially collect pollen that is rich in protein (Regali and Rasmont, 1995;Cook et al, 2005;Kitaoka and Nieh, 2009;Leonhardt and Blüthgen, 2012;Konzmann and Lunau, 2014; but see Pernal and Currie, 2002), suggesting that bees are further able to assess pollen quality (e.g. protein content).…”
Section: Introductionmentioning
confidence: 99%
“…Alaux et al, 2010;Konzmann and Lunau, 2014). Detailed studies on the bees' ability to assess the nutrient concentration of food are, however, still missing.…”
Section: Introductionmentioning
confidence: 99%